2004
DOI: 10.1253/circj.68.923
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma Concentrations of B-Type Natriuretic Peptide With Infarct Size Quantified by Tomographic Thallium-201 Myocardial Scintigraphy in Asymptomatic Patients With Previous Myocardial lnfarction

Abstract: -type (atrial) natriuretic peptide (ANP) and B-type (brain) natriuretic peptide (BNP) are hormones with a wide range of potent biological effects, including natriuresis, diuresis, vasodilatation, and inhibition of the renin -angiotensin -aldosterone and sympathetic nervous systems. 1,2 We and others have shown that ANP is mainly synthesized and secreted from the atria in adult mammals, 1,3-5 but it is also synthesized and secreted from the ventricles in patients with congestive heart failure. [3][4][5] BNP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…It has been reported that the plasma level of BNP increases rapidly and markedly immediately after the onset of AMI, 4 and a more recent study has shown that the BNP level is predictive of infarct size in patients following AMI. 20 The present study found that patients with a longer time-to-treatment interval had a markedly higher plasma NT-proBNP level than those with shorter time-to-treatment interval and that the duration of AMI and a low LVEF (<45%) were independent predictors for elevation of NT-proBNP. Additionally, low LVEF, which has been shown to be a poor prognostic risk factor following AMI, 21 was independently associated with 30-day MACO in this study.…”
Section: Discussionsupporting
confidence: 49%
“…It has been reported that the plasma level of BNP increases rapidly and markedly immediately after the onset of AMI, 4 and a more recent study has shown that the BNP level is predictive of infarct size in patients following AMI. 20 The present study found that patients with a longer time-to-treatment interval had a markedly higher plasma NT-proBNP level than those with shorter time-to-treatment interval and that the duration of AMI and a low LVEF (<45%) were independent predictors for elevation of NT-proBNP. Additionally, low LVEF, which has been shown to be a poor prognostic risk factor following AMI, 21 was independently associated with 30-day MACO in this study.…”
Section: Discussionsupporting
confidence: 49%
“…13 Therefore, baseline levels of BNP and NTproBNP have recently been identified as new and useful biochemical markers both in the differential diagnosis of CHF and in predicting adverse cardiac outcomes after AMI, 3,10,14 infarction size 15 or acute coronary syndrome. 13,16 Ischemic stroke, which is mostly caused by atherothrombotic changes of the cerebrovascular system, has many similarities with coronary artery disease.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In the clinical studies myocardial ischemia augments the synthesis and release of BNP, even in the absence of myocardial necrosis or preexisting left ventricular dysfunction, although the level of expression of the BNP gene in the left ventricle tripled within 4 h of coronary ligation in an animal model. [25][26][27][28] In the present study, we measured the BNP level once, approximately 43 min after cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%